Examination of the usefulness of combined use of DPC and NPWT after emergency laparotomy for lower gastrointestinal perforation - Taniguchi, Yoshiki; Yamaguchi, Eiji; Kato, Junichiro; Fukata, Tadafumi; Ito, Yusuke; Kittaka, Hirotada; Hayashi, Yasuyuki; Fukuzaki, Takayuki; Sawano, Hirotaka; Shingai, Tatsushi (Japanese Journal of Acute Care Surgery, 2022)
【Purpose】 We investigate the usefulness of combined use of Delayed Primary Closure （DPC） and Negative Pressure Wound Therapy （NPWT） after emergency laparotomy for lower gastrointestinal perforation. 【Subjects and Methods】We retrospectively investigated 37 cases of lower gastrointestinal perforation corresponding to Hinchey classification Stage Ⅲ or Ⅳ who underwent emergency laparotomy. We divided 37 patients into a primary closure group and a group in which DPC and NPWT were used in combination. 【Results】 The incidence of Surgical Site Infection （SSI） between the two groups was 31.6％ vs 27.8％ （P＝0.80）, showing no statistically significant difference. However, the incidence of deep incisional SSI between two groups was 21.1％ vs 0.00％ （P＜0.05）, showing a statistically significant difference. 【Conclusion】 In patients who underwent emergency laparotomy for lower gastrointestinal perforation, the combined use of DPC and NPWT may reduce the incidence of deep incisional SSI.